If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = 0 Reorder the terms: -3 + 4x = 0 Solving -3 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 0 + 3 4x = 0 + 3 Combine like terms: 0 + 3 = 3 4x = 3 Divide each side by '4'. x = 0.75 Simplifying x = 0.75
| 2(6ax+y)=11ax-7y | | 0.2(6)+x=0.4(6+x) | | 11-9A-2A=5E-3A-2 | | 4u^2-8u+3=0 | | -3y+7.4=20.9 | | 5X+9=11-5 | | .4x+.2(6)=x+6 | | 6x-(2x-4)=40 | | 4a-(5-a)=3(a+2) | | 6x^2+21x-15=0 | | 9x^2-81=12 | | 0.43=in(y) | | 4/7=m/9 | | (-144)-7x-4y=28 | | 2-7x=-7 | | -7x-4y=28(-144) | | .9x+.25(70)=.8(x+70) | | W=J+Jrt | | 2x^2-200=0 | | 5-5[4-(3y-2)]= | | 5x^2+11x+4=0 | | .33x=29 | | 16xy=52 | | 37c+45=0 | | 0=80t+-16t^2 | | 0=80t-16t | | -1-5(-7w+1)=3(8w-3)+6 | | .6(x+200)=.66x-318 | | 50x+20(60)=40x+2400 | | w(4w-3)-4w(w-5)=w-2 | | 2x+3=1x-9 | | 2/3(x-3)+6=1/6(4x+24) |